The Effect of Teaching Quality and Educational Facilities on Student Satisfaction (Case Study at Subulussalam Islamic Boarding School) - Abdullah Maududie Maimun; Taryono; Sutrisno (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The objective of this research is to investigate the impact of teaching quality and educational facilities on student satisfaction at Subulussalam Islamic Boarding School. This research applies a numerical method with a relational/causal design to test the relationship between independent and dependent variables. Data were collected through the distribution of questionnaires to 72 students as participants using a Likert scale. In addition, observation, documentation, and literature review were carried out to strengthen the research data Data analysis was performed using multiple linear regression analysis in SPSS, starting with validity, reliability, and classical assumption tests. Research findings indicate that teaching quality has a positively and significantly impacts student satisfaction with a significance value of 0.002 < 0.05. Educational facilities also positively and significantly influence student satisfaction with a significance value of 0.001 < 0.05. Teaching quality and educational facilities simultaneously have a significant impact on student satisfaction, indicated with an F-test significance level of 0.000 < 0.05. The determination coefficient analysis shows that these two variables contribute 42.6% to student satisfaction, while the rest 57.4% is impacted by differet factors beyond this research. The findings of this research indicate that improving teaching quality and educational facilities is very crucial in enhancing student contentment and the standard of educational services at Subulussalam Islamic Boarding School.